Engineering plasmonic and dielectric directional nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVIII)
Optical and infrared antennas provide a promising way to couple photons in and out of nanoscale structures. As counterpart to conventional radio antennas, they are able to increase optical felds in sub-wavelength volumes, to enhance excitation and emission of quantum emitters or to direct light, radiated by quantum emitters. The directed emission of these antennas has been mainly pursued by surface plasmon based devices, e.g. Yagi-Uda like antennas, which are rather complicated due to the coupling of several metallic particles. Also, like all metallic structures in optical or infrared regime, these devices are very sensitive to fabrication tolerances and are affected by strong losses. It has been shown recently, that such directed emission can be accomplished by dielectric materials as well. In this paper we present an optimization of nanoscopic antennas in the near infrared regime starting from a metallic Yagi-Uda structure. The optimization is done via a particle-swarm algorithm, using full time domain finite integration simulations to obtain the characteristics of the investigated structure, also taking into account substrates. Furthermore we present a dielectric antenna, which performs even better, due to the lack of losses by an appropriate choice of the dielectric material. These antennas are robust concerning fabrication tolerances and can be realized with different materials for both the antenna and the substrate, without using high index materials.
Keywords: tet_topic_opticalantenna

Analytic moduli spaces of simple sheaves on families of integral curves - Burban, Igor; Kreußler, B. (Mathematische Nachrichten)

Beobachten und Dokumentieren. Basis zur chancengerechten Gestaltung des pädagogischen Alltags - Bruns, Julia; Walter-Laager, C.; Pfiffner, M.; Schwarz, J. (Vorsprung für alle! Erhöhung der Chancengerechtigkeit durch Projekte der Frühpädagogik)

Adaptive Förderung in der elementarpädagogischen Praxis. Eine empirische Studie zum di-daktischen Handeln von Erzieherinnen und Erziehern im Bereich Mathematik - Bruns, Julia

Adaptive mathematische Förderung im Elementarbereich - Empirische Ergebnisse zum didaktischen Handeln von Erzieherinnen - Bruns, Julia; Eichen, Lars (Beiträge zum Mathematikunterricht 2014)

A Scalable Formal Debugging Approach with Auto-Correction Capability based on Static Slicing and Dynamic Ranking for RTL Datapath Designs - Alizadeh, Bijan; Behnam, Payman; Sadeghi-Kohan, Somayeh (IEEE Transactions on Computers)
Keywords: Computational Theory and Mathematics; Hardware and Architecture; Theoretical Computer Science; Software

An off-line MDSI interconnect BIST incorporated in BS 1149.1 - Mohammadi, Marzieh; Sadeghi-Kohan, Somayeh; Masoumi, Nasser; Navabi, Zainalabedin (2014 19th IEEE European Test Symposium (ETS))

Improving polynomial datapath debugging with HEDs - Sadeghi-Kohan, Somayeh; Behnam, Payman; Alizadeh, Bijan; Fujita, Masahiro; Navabi, Zainalabedin (2014 19th IEEE European Test Symposium (ETS))

Verschiebungen an der Grenze zwischen Hardware und Software - Platzner, Marco; Plessl, Christian (Logiken strukturbildender Prozesse: Automatismen)
Im Bereich der Computersysteme ist die Festlegung der Grenze zwischen Hardware und Software eine zentrale Problemstellung. Diese Grenze hat in den letzten Jahrzehnten nicht nur die Entwicklung von Computersystemen bestimmt, sondern auch die Strukturierung der Ausbildung in den Computerwissenschaften beeinﬂusst und sogar zur Entstehung von neuen Forschungsrichtungen geführt. In diesem Beitrag beschäftigen wir uns mit Verschiebungen an der Grenze zwischen Hardware und Software und diskutieren insgesamt drei qualitativ unterschiedliche Formen solcher Verschiebungen. Wir beginnen mit der Entwicklung von Computersystemen im letzten Jahrhundert und der Entstehung dieser Grenze, die Hardware und Software erst als eigenständige Produkte diﬀerenziert. Dann widmen wir uns der Frage, welche Funktionen in einem Computersystem besser in Hardware und welche besser in Software realisiert werden sollten, eine Fragestellung die zu Beginn der 90er-Jahre zur Bildung einer eigenen Forschungsrichtung, dem sogenannten Hardware/Software Co-design, geführt hat. Im Hardware/Software Co-design ﬁndet eine Verschiebung von Funktionen an der Grenze zwischen Hardware und Software während der Entwicklung eines Produktes statt, um Produkteigenschaften zu optimieren. Im fertig entwickelten und eingesetzten Produkt hingegen können wir dann eine feste Grenze zwischen Hardware und Software beobachten. Im dritten Teil dieses Beitrags stellen wir mit selbst-adaptiven Systemen eine hochaktuelle Forschungsrichtung vor. In unserem Kontext bedeutet Selbstadaption, dass ein System Verschiebungen von Funktionen an der Grenze zwischen Hardware und Software autonom während der Betriebszeit vornimmt. Solche Systeme beruhen auf rekonﬁgurierbarer Hardware, einer relativ neuen Technologie mit der die Hardware eines Computers während der Laufzeit verändert werden kann. Diese Technologie führt zu einer durchlässigen Grenze zwischen Hardware und Software bzw. löst sie die herkömmliche Vorstellung einer festen Hardware und einer ﬂexiblen Software damit auf.

Partitioning and Vectorizing Binary Applications for a Reconfigurable Vector Computer - Kenter, Tobias; Vaz, Gavin Francis; Plessl, Christian (Proceedings of the International Symposium on Reconfigurable Computing: Architectures, Tools, and Applications (ARC))
In order to leverage the use of reconfigurable architectures in general-purpose computing, quick and automated methods to find suitable accelerator designs are required. We tackle this challenge in both regards. In order to avoid long synthesis times, we target a vector copro- cessor, implemented on the FPGAs of a Convey HC-1. Previous studies showed that existing tools were not able to accelerate a real-world application with low effort. We present a toolflow to automatically identify suitable loops for vectorization, generate a corresponding hardware/software bipartition, and generate coprocessor code. Where applicable, we leverage outer-loop vectorization. We evaluate our tools with a set of characteristic loops, systematically analyzing different dependency and data layout properties.

Seven Recipes for Setting Your FPGA on Fire – A Cookbook on Heat Generators - Agne, Andreas; Hangmann, Hendrik; Happe, Markus; Platzner, Marco; Plessl, Christian (Microprocessors and Microsystems)
Due to the continuously shrinking device structures and increasing densities of FPGAs, thermal aspects have become the new focus for many research projects over the last years. Most researchers rely on temperature simulations to evaluate their novel thermal management techniques. However, these temperature simulations require a high computational effort if a detailed thermal model is used and their accuracies are often unclear. In contrast to simulations, the use of synthetic heat sources allows for experimental evaluation of temperature management methods. In this paper we investigate the creation of significant rises in temperature on modern FPGAs to enable future evaluation of thermal management techniques based on experiments. To that end, we have developed seven different heat-generating cores that use different subsets of FPGA resources. Our experimental results show that, according to external temperature probes connected to the FPGA’s heat sink, we can increase the temperature by an average of 81 !C. This corresponds to an average increase of 156.3 !C as measured by the built-in thermal diodes of our Virtex-5 FPGAs in less than 30 min by only utilizing about 21 percent of the slices.

Reconstructing AES Key Schedules from Decayed Memory with FPGAs - Riebler, Heinrich; Kenter, Tobias; Plessl, Christian; Sorge, Christoph (Proceedings of Field-Programmable Custom Computing Machines (FCCM))
In this paper, we study how AES key schedules can be reconstructed from decayed memory. This operation is a crucial and time consuming operation when trying to break encryption systems with cold-boot attacks. In software, the reconstruction of the AES master key can be performed using a recursive, branch-and-bound tree-search algorithm that exploits redundancies in the key schedule for constraining the search space. In this work, we investigate how this branch-and-bound algorithm can be accelerated with FPGAs. We translated the recursive search procedure to a state machine with an explicit stack for each recursion level and create optimized datapaths to accelerate in particular the processing of the most frequently accessed tree levels. We support two different decay models, of which especially the more realistic non-idealized asymmetric decay model causes very high runtimes in software. Our implementation on a Maxeler dataflow computing system outperforms a software implementation for this model by up to 27x, which makes cold-boot attacks against AES practical even for high error rates.
Keywords: coldboot

Self-awareness as a Model for Designing and Operating Heterogeneous Multicores - Agne, Andreas; Happe, Markus; Lösch, Achim; Plessl, Christian; Platzner, Marco (ACM Transactions on Reconfigurable Technology and Systems (TRETS))
Self-aware computing is a paradigm for structuring and simplifying the design and operation of computing systems that face unprecedented levels of system dynamics and thus require novel forms of adaptivity. The generality of the paradigm makes it applicable to many types of computing systems and, previously, researchers started to introduce concepts of self-awareness to multicore architectures. In our work we build on a recent reference architectural framework as a model for self-aware computing and instantiate it for an FPGA-based heterogeneous multicore running the ReconOS reconfigurable architecture and operating system. After presenting the model for self-aware computing and ReconOS, we demonstrate with a case study how a multicore application built on the principle of self-awareness, autonomously adapts to changes in the workload and system state. Our work shows that the reference architectural framework as a model for self-aware computing can be practically applied and allows us to structure and simplify the design process, which is essential for designing complex future computing systems.

ReconOS - An Operating System Approach for Reconfigurable Computing - Agne, Andreas; Happe, Markus; Keller, Ariane; Lübbers, Enno; Plattner, Bernhard; Platzner, Marco; Plessl, Christian (IEEE Micro)
The ReconOS operating system for reconfigurable computing offers a unified multi-threaded programming model and operating system services for threads executing in software and threads mapped to reconfigurable hardware. The operating system interface allows hardware threads to interact with software threads using well-known mechanisms such as semaphores, mutexes, condition variables, and message queues. By semantically integrating hardware accelerators into a standard operating system environment, ReconOS allows for rapid design space exploration, supports a structured application development process and improves the portability of applications

Runtime Resource Management in Heterogeneous System Architectures: The SAVE Approach - C. Durelli, Gianluca; Pogliani, Marcello; Miele, Antonio; Plessl, Christian; Riebler, Heinrich; Vaz, Gavin Francis; D. Santambrogio, Marco; Bolchini, Cristiana (Proc. Int. Symp. on Parallel and Distributed Processing with Applications (ISPA))

Deferring Accelerator Offloading Decisions to Application Runtime - Vaz, Gavin Francis; Riebler, Heinrich; Kenter, Tobias; Plessl, Christian (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Reconfigurable architectures provide an opportunityto accelerate a wide range of applications, frequentlyby exploiting data-parallelism, where the same operations arehomogeneously executed on a (large) set of data. However, whenthe sequential code is executed on a host CPU and only dataparallelloops are executed on an FPGA coprocessor, a sufficientlylarge number of loop iterations (trip counts) is required, such thatthe control- and data-transfer overheads to the coprocessor canbe amortized. However, the trip count of large data-parallel loopsis frequently not known at compile time, but only at runtime justbefore entering a loop. Therefore, we propose to generate codeboth for the CPU and the coprocessor, and to defer the decisionwhere to execute the appropriate code to the runtime of theapplication when the trip count of the loop can be determinedjust at runtime. We demonstrate how an LLVM compiler basedtoolflow can automatically insert appropriate decision blocks intothe application code. Analyzing popular benchmark suites, weshow that this kind of runtime decisions is often applicable. Thepractical feasibility of our approach is demonstrated by a toolflowthat automatically identifies loops suitable for vectorization andgenerates code for the FPGA coprocessor of a Convey HC-1. Thetoolflow adds decisions based on a comparison of the runtimecomputedtrip counts to thresholds for specific loops and alsoincludes support to move just the required data to the coprocessor.We evaluate the integrated toolflow with characteristic loopsexecuted on different input data sizes.

Kernel-Centric Acceleration of High Accuracy Stereo-Matching - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Stereo-matching algorithms recently received a lot of attention from the FPGA acceleration community. Presented solutions range from simple, very resource efficient systems with modest matching quality for small embedded systems to sophisticated algorithms with several processing steps, implemented on big FPGAs. In order to achieve high throughput, most implementations strongly focus on pipelining and data reuse between different computation steps. This approach leads to high efficiency, but limits the supported computation patterns and due the high integration of the implementation, adaptions to the algorithm are difficult. In this work, we present a stereo-matching implementation, that starts by offloading individual kernels from the CPU to the FPGA. Between subsequent compute steps on the FPGA, data is stored off-chip in on-board memory of the FPGA accelerator card. This enables us to accelerate the AD-census algorithm with cross-based aggregation and scanline optimization for the first time without algorithmic changes and for up to full HD image dimensions. Analyzing throughput and bandwidth requirements, we outline some trade-offs that are involved with this approach, compared to tighter integration of more kernel loops into one design.

SAVE: Towards efficient resource management in heterogeneous system architectures - C. Durelli, Gianluca; Copolla, Marcello; Djafarian, Karim; Koranaros, George; Miele, Antonio; Paolino, Michele; Pell, Oliver; Plessl, Christian; D. Santambrogio, Marco; Bolchini, Cristiana (Proc. Int. Conf. on Reconfigurable Computing: Architectures, Tools and Applications (ARC))

Accelerating Finite Difference Time Domain Simulations with Reconfigurable Dataflow Computers - Giefers, Heiner; Plessl, Christian; Förstner, Jens (ACM SIGARCH Computer Architecture News)
Keywords: funding-maxup; tet_topic_hpc

The project virtual science fair for promoting inquiry learning - Jonas-Ahrend, Gabriela (Initiatives in mathematics and science education with global implications)

Raising students’ interest in STEM and encouraging career choice in science and engineering - Jonas-Ahrend, Gabriela; Rafaeli-Mishkin, Hagit; Wengrovicz, Niva; Dori, Yehudit Judy

A combined hardware-software approach for acoustic sensor network synchronization - Schmalenstroeer, Joerg; Jebramcik, Patrick; Haeb-Umbach, Reinhold (Signal Processing)
Abstract In this paper we present an approach for synchronizing a wireless acoustic sensor network using a two-stage procedure. First the clock frequency and phase differences between pairs of nodes are estimated employing a two-way message exchange protocol. The estimates are further improved in a Kalman filter with a dedicated observation error model. In the second stage network-wide synchronization is achieved by means of a gossiping algorithm which estimates the average clock frequency and phase of the sensor nodes. These averages are viewed as frequency and phase of a virtual master clock, to which the clocks of the sensor nodes have to be adjusted. The amount of adjustment is computed in a specific control loop. While these steps are done in software, the actual sampling rate correction is carried out in hardware by using an adjustable frequency synthesizer. Experimental results obtained from hardware devices and software simulations of large scale networks are presented.
Keywords: Gossip algorithm

A Gossiping Approach to Sampling Clock Synchronization in Wireless Acoustic Sensor Networks - Schmalenstroeer, Joerg; Jebramcik, Patrick; Haeb-Umbach, Reinhold (39th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2014))
"In this paper we present an approach for synchronizing the sampling clocks of distributed microphones over a wireless network. The proposed system uses a two stage procedure. It first employs a two-way message exchange algorithm to estimate the clock phase and frequency difference between two nodes and then uses a gossiping algorithmto estimate a virtual master clock, to which all sensor nodes synchronize. Simulation results are presented for networks of different topology and size, showing the effectiveness of our approach."

Online Observation Error Model Estimation for Acoustic Sensor Network Synchronization - Schmalenstroeer, Joerg; Zhao, Weile; Haeb-Umbach, Reinhold (11. ITG Fachtagung Sprachkommunikation (ITG 2014))
"Acoustic sensor network clock synchronization via time stamp exchange between the sensor nodes is not accurate enough for many acoustic signal processing tasks, such as speaker localization. To improve synchronization accuracy it has therefore been proposed to employ a Kalman Filter to obtain improved frequency deviation and phase offset estimates. The estimation requires a statistical model of the errors of the measurements obtained from the time stamp exchange algorithm. These errors are caused by random transmission delays and hardware effects and are thus network specific. In this contribution we develop an algorithm to estimate the parameters of the measurement error model alongside the Kalman filter based sampling clock synchronization, employing the Expectation Maximization algorithm. Simulation results demonstrate that the online estimation of the error model parameters leads only to a small degradation of the synchronization performance compared to a perfectly known observation error model."

Cell Mapping Techniques for Exploratory Landscape Analysis - Kerschke, Pascal; Preuss, Mike; Hernández, Carlos; Schütze, Oliver; Sun, Jian-Qiao; Grimme, Christian; Rudolph, Günter; Bischl, Bernd; Trautmann, Heike (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation V)
Exploratory Landscape Analysis is an effective and sophisticated approach to characterize the properties of continuous optimization problems. The overall aim is to exploit this knowledge to give recommendations of the individually best suited algorithm for unseen optimization problems. Recent research revealed a high potential of this methodology in this respect based on a set of well-defined, computable features which only requires a quite small sample of function evaluations. In this paper, new features based on the cell mapping concept are introduced and shown to improve the existing feature set in terms of predicting expert-designed high-level properties, such as the degree of multimodality or the global structure, for 2-dimensional single objective optimization problems.

A Multiobjective Evolutionary Algorithm Guided by Averaged Hausdorff Distance to Aspiration Sets - Rudolph, G; Schütze, O; Grimme, C; Trautmann, Heike (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation V)
The incorporation of expert knowledge into multiobjective optimization is an important issue which in this paper is reflected in terms of an aspiration set consisting of multiple reference points. The behaviour of the recently introduced evolutionary multiobjective algorithm AS-EMOA is analysed in detail and comparatively studied for bi-objective optimization problems w.r.t. R-NSGA2 and a respective variant. It will be shown that the averaged Hausdorff distance, integrated into AS-EMOA, is an efficient means to accurately approximate the desired aspiration set.

An Aspiration Set EMOA Based on Averaged Hausdorff Distances - Rudolph, Günter; Grimme, Christian; Schütze, Oliver; Trautmann, Heike (Proceedings of the Learning and Intelligent OptimizatioN Conference (LION 8))
We propose an evolutionary multiobjective algorithm that approximates multiple reference points (the aspiration set) in a single run using the concept of the averaged Hausdorff distance.

Stopping Criteria for Multimodal Optimization - Wessing, S; Preuss, M; Trautmann, Heike (Proceedings of the Parallel Problem Solving from Nature — PPSN XIII)
Multimodal optimization requires maintenance of a good search space coverage and approximation of several optima at the same time. We analyze two constitutive optimization algorithms and show that in many cases, a phase transition occurs at some point, so that either diversity collapses or optimization stagnates. But how to derive suitable stopping criteria for multimodal optimization? Experimental results indicate that an algorithm’s population contains sufficient information to estimate the point in time when several performance indicators reach their optimum. Thus, stopping criteria are formulated based on summary characteristics employing objective values and mutation strength.

Why eve and mallory (also) love webmasters - Fahl, Sascha; Acar, Yasemin; Perl, Henning; Smith, Matthew (Proceedings of the 9th ACM symposium on Information, computer and communications security)

Handlungsbedarf in fachmathematischen Veranstaltungen? – Spezielle Maßnahmen an der Universität Paderborn - Panse, Anja; Hilgert, Joachim; Hoffmann, Max (Beiträge zum Mathematikunterricht 2014)

Minimal representations via Bessel operators - Hilgert, Joachim; Möllers, J.; Kobayashi, T. (J. Math. Soc. Japan)

Singular superspaces - Hilgert, Joachim; Wurzbacher, T.; Alldridge, A. (Math. Z.)

The Radon transform and its dual for limits of symmetric spaces - Hilgert, Joachim; Ólafsson, G. (Developments and Retrospectives in Lie Theory - Geometric and Analytic Methods)

Schwierigkeiten von Studienanfängern, verschiedene Lehrmethoden und Fragen an die Didaktik - Hilgert, Joachim; Hoffmann, M.; Panse, A. (Beiträge zum Mathematikunterricht 2014)

Resonances for the Laplacian on Riemannian symmetric spaces: the case of SL(3,R)/SO(3) - Hilgert, Joachim; Pasquale, A.; Przebinda, T.

Robust Preconditioning Estimates for Convection-Dominated Elliptic Problems via a Streamline Poincaré--Friedrichs Inequality - Axelsson, Owe; Karátson, János; Kovács, Balázs (SIAM Journal on Numerical Analysis)
Keywords: Numerical Analysis; Applied Mathematics; Computational Mathematics

On the numerical performance of a sharp a posteriori error estimator for some nonlinear elliptic problems - Kovács, Balázs (Applications of Mathematics)
Keywords: Applied Mathematics

Ziehen und Beweisen mit DGS. Welche Beweiskraft haben für Studierende die Erkenntnisse, die sie im Zugmodus gewinnen? - Werth, Gerda

Discontinuity of the Fuglede-Kadison determinant on a group von Neumann algebra - Küster, Benjamin (Communications in Mathematics)

Fach-und sprachintegrierte Förderung durch Darstellungsvernetzung und Scaffolding: ein Entwicklungsforschungsprojekt zum Anteilbegriff - Wessel, Lena

HeroeS - A Framework for Heterogeneous Software-Intensive System Design with SystemC - Becker, Markus; Müller, Wolfgang; Stroop, Joachim; Kiffmeier, Ulrich (Design, Automation and Test in Europe DATE, University Booth, Dresden)

Probabilistic Analysis of Long-term Swarm Performance under Spatial Interferences - Khaluf, Yara; Birattari, Mauro; Rammig, Franz-Josef (Theory and Practice of Natural Computing, Nr. 8273, 2nd International Conference on the Theory and Practice of Natural Computing, TPNC 2013)

Early Phase Memory Leak Detection in Embedded Software Designs with Virtual Memory Management Model - Joy, M. tech. Mabel Mary; Müller, Wolfgang; Rammig, Franz-Josef (Proceedings of AVICPS 2013, Dez. 2013 IEEE Computer Society,)

AN ENERGY-EFFICIENT HEURISTIC FOR HARD REAL- TIME SYSTEM ON MULTI-CORE PROCESSORS - He, Da; Müller, Wolfgang (Proceedings of International Conference on Applied Computing (AC))

Aspect-Oriented Model-Driven Engineering for Embedded Systems Applied to Automation Systems - Wehrmeister, Marco A.; Pereira, Carlos E.; Rammig, Franz-Josef (IEEE Trans. on Industrial Informatics vol. 9 (no. 4))
Automation and control systems include many “intelligent” automation devices, which are usually implemented as complex embedded systems. New methods and tools are demanded to cope with the increasing design complexity, while keeping the project on schedule. Proper handling of nonfunctional system requirements is a key factor during the design of industrial automation systems, since in some application domains they are as important as (sometimes, more important than) functional requirements. This paper presents a model-driven engineering approach, which combines Unified Modeling Language (UML) and aspect-oriented software development (AOSD) to design real-time and embedded automation systems. The proposed approach allows a smooth transition from the initial phases to implementation by using software tools, comprising the system specification and the automatic generation of source code. By combining UML with model-level aspects and a script-base code generation tool, it enables the use of AOSD during system design and implementation, even though the target platform does not natively support such concepts. Experimental results on using this approach to design real-world examples of automation systems are presented. The results indicate a positive impact on the design of automation systems. The encapsulation of nonfunctional requirements was improved, increasing the reuse of developed artifacts. Generated source code statistics indicate that the proposed approach can generated a fair amount of code per model element.

Task Allocation Strategy for Time-Constrained Tasks in Robots Swarms - Khaluf, Yara; Rammig, Franz-Josef (ECAL 2013, 12th European Conference on Artificial Life)

Simulationsgestützter Entwurf für Elektrofahrzeuge - Farshizadeh, Emad; Briese, Herrmann; Steinmann, David; Stockmann, Lars; Beringer, Steffen; Holler, Dominik; Klobedanz, Kay; Heinzemann, Christian; Peter, Klaus; Leuer, Michael (8. Dortmunder Autotag, Sep. 2013)
Das Thema Elektromobilität hat in der Fahrzeugindustrie in den letzten Jahren viel Aufmerksamkeit erhalten. Gerade im Bereich der Entwicklung von Steuergeräte-Software ist der Bedarf an frühzeitiger Absicherung hoch. Nur so können Produkteinführungszeiten minimiert und effektiv Entwicklungskosten eingespart werden. Komplexe Werkzeugketten und die verteilte Entwicklung erschweren den Prozess und verlängern die Entwicklungszeit. Das Förderprojekt „Simulationsgestützter Entwurf für Elektrofahrzeuge“, kurz „E-Mobil“, nimmt sich der Herausforderungen einer verteilten Entwicklung von Steuergeräte-Software an. Vier Projektpartner aus Industrie und Forschung untersuchen die Besonderheiten sowohl bzgl. des Entwurfsprozesses, als auch der beteiligten Entwurfswerkzeuge im Vergleich zur konventionellen Fahrzeugentwicklung. Im Fokus stehen die Modellierung und die simulationsgestützte Absicherung in frühen Entwurfsstadien. Die Modellierung umfasst Regelungssoftware sowie die für die Simulation nötigen elektrischen und mechatronischen Komponenten. Die vorliegende Arbeit stellt die Kernthemen sowie aktuelle Ergebnisse aus dem Projekt vor.

Efficient Power Intent Validation Using Loosely-Timed Simulation Models - Mischkalla, Fabian; Müller, Wolfgang (23rd International Workshop on Power And Timing Modeling, Optimization and Simulation, Sep. 2013)

Learning Recommendation System for Automated Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 10th IEEE International Conference on Services Computing (SCC))
The as a Service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilized on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our general idea of modeling this service composition and recommendation process as Markov Decision Process and of solving it by means of Reinforcement Learning. A case study serves as proof of concept.

Proteus Hypervisor: Full Virtualization and Paravirtualization for Multi-Core Embedded Systems - Gilles, Katharina; Grösbrink, Stefan; Baldin, Daniel; Kerstan, Timo (International Embedded Systems Symposium, 17. - 19. Jun. 2013)

On the Homogeneous Multiprocessor Virtual Machine Partitioning Problem - Grösbrink, Stefan (International Embedded Systems Symposium, 17. - 19. Jun. 2013)

Organic Real-time Programming – Vision and Approaches towards Self-Evolving and Adaptive Real-time Software - Rammig, Franz-Josef; Khaluf, Lial; Montealegre, Norma; Stahl, Katharina; Zhao, Yuhong (Proc. 9th Workshop on Software Technologies for Future Embedded and Ubiquitous Systems (SEUS) 2013)

HeroeS: Virtual Platform Driven Integration of Heterogeneous Software Components for Multi-Core Real-Time Architectures - Becker, Markus; Kiffmeier, Ulrich; Müller, Wolfgang (16th IEEE Computer Society Symposium on Object/Component/Service-oriented Real-time Distributed Computing)

A Framework for Enhancing Dependability in Self-x Systems by Artificial Immune Systems - Rammig, Franz-Josef; Stahl, Katharina; Vaz, Gavin Francis (Proc. 4th IEEE Workshop on Self-Organizing Real-Time Systems (SORT) 2013)

Multilevel Planning for Self-Optimizing Mechatronic Systems - Rasche, Christoph; Ziegert, Steffen (Proceedings of The Fifth International Conference on Adaptive and Self-Adaptive Systems and Applications)

AIS-based Anomaly Detection for Self-X Systems - Stahl, Katharina (Proceedings of the First Organic Computing Doctoral Dissertation Colloquium (OC-DDC'13))

Safe Self-Evolving Embedded Software via System Virtualization - Grösbrink, Stefan; Rammig, Franz-Josef (3rd SBC Workshop on Autonomic Distributed Systems - WoSiDA 2013)

Fair Bandwidth Sharing among Virtual Machines in a Multi-criticality Scope - Grösbrink, Stefan; Almeida, Luis; de Sousa, Mario; Petters, Stefan M. (5th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2013))

Accelerating Online Model Checking - Qanadilo, Mona; Samara, Sufyan; Zhao, Yuhong (6'th Latin-American Symposium on Dependable Computing (LADC 2013))

Bildangereicherte Kartenerstellung zur Unterstützung bei Rettungseinsätzen - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Statistisches Planen in einem realen Roboterszenario - Rasche, Christoph; Bieshaar, Maarten; Jungmann, Alexander; Kleinjohann, Lisa; Kleinjohann, Bernd (Entwurf mechatronischer Systeme, Verlagsschriftenreihe des Heinz Nixdorf Instituts, Paderborn, Band 310)

Architecture for Adaptive Resource Assignment to Virtualized Mixed-Criticality Real-Time Systems - Grösbrink, Stefan; Baldin, Daniel; Oberthür, Simon (ACM SIGBED Review, Band 10)

SystemC Verification Components - An enhanced OVM/UVM for SystemC - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (edaWorkshop 13)

Funktionale Verifikation von Low-Power Designs unter Verwendung Virtueller Prototypen - Mischkalla, Fabian; Müller, Wolfgang (Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV))

SC OVM: An Advanced SystemC Library for OVM-based Verification - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (Open SANITAS SystemC Verification Workshop)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Müller, Wolfgang (ForschungsForum Paderborn)

Basics of Virtual Machine Migration on Heterogeneous Architectures for Self-optimizing Mechatronic Systems - Necessary Conditions and Implementation Issues - Grösbrink, Stefan (Production Engineering Research & Development 7(1))

Learning Service Recommendations - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa (International Journal of Business Process Integration and Management 6(4))
The as a service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilised on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our approach of modelling this service composition and recommendation process as Markov decision process and of solving it by means of reinforcement learning. A case study serves as proof of concept.

Systematic Application of UCIS to Improve the Automation on Verification Closure - Kuznik, Christoph; Oliveira, Marcio F.; Defo, Bertrand; Müller, Wolfgang (Proceedings of DVCON)

A 3D Path Planning Approach Extended by Bifurcation Theory for Formation Flights - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (Recent Advances in Robotics and Automation, Studies in Computational Intelligence, Band 480)
After big disasters, search and rescue missions take place. During these missions it is essential to obtain an overview of the overall situation to arrange efficient rescue tasks as soon as possible. Afterwards, this information has to be continuously updated during the complete mission in order to quickly respond to changing conditions. The use of unmanned aerial vehicles (UAVs) is a viable choice to obtain such an overview in a fast and efficient way. Using multiple UAVs, the problem of coordination has to be solved to decrease the time needed to explore an area. We present an approach for the coordination of UAVs by setting up formation patterns using bifurcation theory. We combine this theory with a potential field approach for exploration, based on harmonic functions.

Fault-Tolerant Deployment of Real-Time Software in AUTOSAR ECU Networks - Klobedanz, Kay; Jatzkowski, Jan; Rettberg, Achim; Müller, Wolfgang (International Embedded Systems Symposium (IESS) 2013)

Automatic Reconstruction of Polygonal Room Models from 3D Point Clouds - Mertsching, Bärbel; Divband Soorati, Mohammad; Kotthauser, Tobias (IEEE International Conference on Robotics and Biomimetics (ROBIO))

Time delay implies cost on task switching: A model to investigate the efficiency of task partitioning - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas (Bulletin of Mathematical Biology)

Algorithmic Requirements for Swarm Intelligence in Differently Coupled Collective Systems - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Zahadat, Payam (Chaos, Solitons & Fractals)

Virtual Spatiality in Agent Controllers: Encoding Compartmentalization - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Schwarzer, Christopher; Michiels, Nico K.; Esparcia-Alcazar, Anna Isabel (Applications of Evolutionary Computation - 16th European Conference (EvoApplications 2013))

A Reductionist Approach to Hypothesis-Catching for the Analysis of Self-Organizing Decision-Making Systems - Hamann, Heiko (7th IEEE Int. Conf. on Self-Adaptive and Self-Organizing Systems (SASO 2013))

Speciation Dynamics: Generating Selective Pressure Towards Diversity - Hamann, Heiko; Lio, Pietro; Miglino, Orazio; Nicosia, Giuseppe; Nolfi, Stefano; Pavone, Mario (12th European Conference on Artificial Life (ECAL 2013))

Towards Swarm Calculus: Urn Models of Collective Decisions and Universal Properties of Swarm Performance - Hamann, Heiko (Swarm Intelligence)

Themenmodellierung zur Identifikation und Gruppierung von Spam-Webseiten - Laudemann, Stefan

Nichtapproximierbarkeitsresultate zu Radius- und Durchmesserclustering unter Verwendung von L_p-Metriken - Leder, Lennart

A heuristic energy-aware approach for hard real-time systems on multi-core platforms - He, Da; Müller, Wolfgang (Microprocessors and Microsystems - Embedded Hardware Design 37(6-7))

Embedded Systems: Design, Analysis and Verification. Proceedings of the 4th IFIP TC10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 2013

Organic Programming of Real-Time Operating Systems - Khaluf, Lial; Rammig, Franz-Josef (The Ninth International Conference on Autonomic and Autonomous Systems)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Learning Efficient Information Extraction on Heterogeneous Texts - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the Sixth International Joint Conference on Natural Language Processing)

Information Extraction as a Filtering Task - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the 22nd ACM International Conference on Conference on Information & Knowledge Management)

Automatic Pipeline Construction for Real-Time Annotation - Wachsmuth, Henning; Rose, Mirko; Engels, Gregor (14th International Conference on Intelligent Text Processing and Computational Linguistics)

Practical algorithms for clustering and modeling large data sets - Analysis and improvements - Kuntze, Daniel

An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (J. Cryptology)

Practical Signatures from Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Hong Seo, Jae; Striecks, Christoph (Advances in Cryptology - EUROCRYPT 2013, 32nd Annual International Conference on the Theory and Applications of Cryptographic Techniques, Athens, Greece, May 26-30, 2013. Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Bounded Model Checking of Graph Transformation Systems via SMT Solving - Isenberg, Tobias; Steenken, Dominik; Wehrheim, Heike (Formal Techniques for Distributed Systems - Joint IFIP WG 6.1 International Conference, {FMOODS/FORTE} 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings)

SPIN as a Linearizability Checker under Weak Memory Models - Travkin, Oleg; Mütze, Annika; Wehrheim, Heike (Hardware and Software: Verification and Testing - 9th International Haifa Verification Conference, HVC 2013, Haifa, Israel, November 5-7, 2013, Proceedings)

A High-Level Semantics for Program Execution under Total Store Order Memory - Dongol, Brijesh; Travkin, Oleg; Derrick, John; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2013 - 10th International Colloquium, Shanghai, China, September 4-6, 2013. Proceedings)

Temporal Reconfiguration Plans for Self-Adaptive Systems - Ziegert, Steffen; Wehrheim, Heike (Software Engineering 2013: Fachtagung des GI-Fachbereichs Softwaretechnik, 26. Februar - 2. März 2013 in Aachen)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut